Verbal-Visual Means of Representing Gender Stereotypes in Modern Advertising - M. V. Terskikh (Научный диалог, 2019)
The article is devoted to the study of the features of verbal and visual representation of gender images in modern advertising texts. The relevance of the study is determined by the high acting potential of advertising as a regulator of behavior in society: advertising often becomes a model for the formation of life images, symbolic codes of social values that orient the individual, manage it, including the gender aspect. The author notes that advertising, on the one hand, uses social standards and stereotypes that have already been formed in society, and on the other, through gender advertising images it represents the consumer modern relations between the sexes, dictating a certain behavior model. As the material for the study, modern advertising videos (2015-2019) were chosen as multicode texts with great persuasive capabilities due to the simultaneous use of verbal, visual, and audio channels of perception. The author of the article relies on previously identified gender images in advertising by linguists, sociologists, psychologists, at the same time it is proposed to consider new images that have not yet become the subject of research. The variability of ideas about femininity and masculinity in the modern world is emphasized. The author develops a typology of gender advertising images.